Decrease of the 3,4-Dihydroxyphenylalanine (DOPA) Decarboxylase Activities in Human Erythrocytes and Mouse Tissues after Administration of DOPA - Tate, Suresh S. (1971)
Human erythrocytes have been found to contain appreciable amounts of DOPA decarboxylase (EC 4.1.1.26) activity. The enzyme activity in erythrocytes from patients with Parkinson's disease who were treated with DOPA was significantly lower than that of untreated patients and of normal individuals. Administration of the drug to mice led to a marked decrease of DOPA decarboxylase in liver and kidney, but not of the brain enzyme. The findings thus indicate that administration of DOPA leads to a decrease in peripheral DOPA decarboxylase, an effect that is expected to be of benefit in DOPA therapy of patients with Parkinson's disease. Peripheral DOPA decarboxylase concentration also decreases in mice after short periods of fasting; the findings suggest that the peripheral enzyme activities may be affected by various nutritional and perhaps hormonal influences, which may be partially responsible for the observed fluctuations in the motor abilities of Parkinsonian patients receiving constant doses of the drug. Study of DOPA decarboxylase activity in erythrocytes may be useful in following changes in patients receiving DOPA therapy and may also be of general interest and value in investigations of catecholamine metabolism in man.